HYDROGEN ADSORPTION ON SILVER CATHODES IN PERCHLORIC ACID SOLUTIONS (Journal of Sciences, Islamic Republic of Iran)
In this paper studies of overvoltage and capacitance measurements at silver cathodes in aqueous perchloric acid at room temperature are described. Capacitances were deduced from open-circuit potential decay measurements. The increase of overvoltage and the growth of the measured capacitances in the course of electrolysis are attributed to a growing pseudocapacitance component. This is analysed in terms of an increasing coverage, ? ,of the cathode by adsorbed hydrogn atoms. The increase in surface coverage from the beginning up to several days of cathodisation ranged up to 2% of a monolayer for silver in 0.1 mol HC1 ,and up toO.9% of a monolayer in 1 mol 1-' HCIO,. The increase in overvoltage at constant current density and the increase in electrode capacitance at constant overvoltage with the logarithm of the cathodic charge (-Q) were linear up to Q values of about -60° C . This increase in overvoltage and pseudocapacitance might be attributed to the adsorption and absorption of hydrogen atoms by silver cathodes